Urgensi dan Relevansi Pembelajaran Kitab Adab Al-'Alim Wa Al-Muta'alim Karya KH. M. Hasyim Asy'ari dalam Membentuk Moral Siswa - Ibnu Mundhir; Ali Mahsun (Universitas Hasyim Asy'ari (UNHASY) Tebuireng Jombang, 2018)
Research about moral is very important to continue to do and improve. Student morals must be established as early as possible through a variety of moral learning as a provision for their souls to face life's challenges and times. Learning the book of Adab Al-Amlim Wa Al-Muta'allim is very instrumental and relevant because its compilation is based on the study of Al-Qura'an, As-Sunnah, and general public habits. This study aims to determine the urgency and relevance of the learning of the book of Adab Al-Amlim Wa Al-Muta'allim written by KH. M. Hasyim Asyari in shaping student morale, learning process, and analysis of supporting and inhibiting factors in learning. This type of research is qualitative descriptive with a case study approach at MA Al-Hidayah Termas Nganjuk. Data collection techniques use observation, interviews, and documentation. This study produced three conclusions, namely: 1) The learning of the book Adab al-limAlim Wa al-Muta'allim is very urgent in relation to the psychological conditions of students who are still unstable and very relevant because they are in the cultured environment of pesantren under the care of a kyai. 2) The learning process of the book Adab al-’Alim Wa al-Muta'allim is emphasized on structured, planned cognitive, affective, and psychomotor abilities because it uses RPP, still synergizes the educational trilogy and learning evaluation routines every three months. 3) Supporting factors in learning include factors that educate pesantren graduates who deserve to be devoted, good pesantren culture, Takhassus exams in order to find out as well as assess how far students are able to learn and practice books, and religious activities that are directly related to student morale. While the inhibiting factors are limited learning time in madrasas and junior high school students who have not been able to read and write Arabic scripts